Mortality from Cardiovascular Diseases: A Comparative Analysis between the Medical and Non-Medical Populations in Brazil - Matos,Giulia Guimarães (2022)
Abstract Background: Cardiovascular disease (CVD) is the leading cause of death worldwide, including among physicians. Professional peculiarities increase cardiovascular risk in this population, making it relevant to analyze mortality in the medical population (MPop) and non-medical population (NMPop). Objectives: To compare the CVD mortality coefficient (MC) in between MPop and NMPop in Brazil by analyzing the epidemiological profile and the main causes of deaths from CVD. Methods: Time-series study with data obtained from the Mortality Information System of the Federal Council of Medicine and the Brazilian Institute of Geography and Statistics, from 2014 to 2018. The variables age group, sex, race, occupation, and CVD that caused the death were assessed in MPop and NMPop. MC, relative risk and odds ratio between the populations were calculated. Tests for difference in proportions, with approximation to the normal distribution, and chi-squared tests were performed, assuming p<0.01 as statistically significant. Results: Both MPop and NMPop had a predominance of men (86.7% and 52.3%), senior citizens (85.9% and 79.7%) and white individuals (86.4% and 52.2%). The MCs of the MPop and NMPop was 92.2 and 255.1 deaths/100,000 individuals, respectively. The main cause of death was acute myocardial infarction (AMI) (32.5% and 24.6% in MPop and NMPop, respectively) followed by cerebrovascular accident (CVA) (5.1% and 10.5% in MPop and NMPop, respectively). Conclusion: In Brazil, mortality from CVD was more prevalent in white elderly males, and mainly caused by AMI and CVA. Being a doctor, man and over 60 years old represents a greater chance of death from CVD in comparison with non-physicians.